THE INFLUENCE OF KNOWLEDGE AND PROMOTION ON THE INTEREST OF THE PEOPLE OF PAYAGOTI VILLAGE, PORTIBI DISTRICT USING SHARIA BANK PRODUCTSTHE INFLUENCE OF KNOWLEDGE AND PROMOTION ON THE INTEREST OF THE PEOPLE OF PAYAGOTI VILLAGE, PORTIBI DISTRICT USING SHARIA BANK PRODUCTS - Windari, Windari; Batubara, Sarmiana; Duma, Duma; Hamna, Fitri (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This research is motivated by the lack of knowledge and promotion of society about Islamic banks is still minimal so that the people of Payagoti Village understand more about conventional banks. So that more people use traditional bank products compared to sharia even though the community already knows that these conventional banks contain usury, so the problem formulation in this study is whether or not the influence of knowledge and promotion simultaneously influences the interests of the people of Payagoti Village, Portibi District using Islamic bank products. The purpose of this study was to determine the effect of knowledge and promotion directly affect the interests of the people of Payagoti Village, Portibi Subdistrict using Islamic banking products. The theory used in this research is about the understanding of Islamic banks, Islamic bank products, fundraising products, fund distribution products, knowledge, promotions, and interests. This research is quantitative research. The data source used is primary data. Data collection techniques used were interviews and questionnaires with a sample of 86 people—data processing using SPSS 23. The analysis technique used is the validity test, reliability test, normality test, classic assumption test, multiple linear regression analysis, coefficient of determination, and hypothesis testing.The results showed that the knowledge and promotion variables simultaneously had an influence on the community's interest in Payagoti Village, Portibi Subdistrict using Islamic bank products.